Utilization of Mustard and CabbageWastesFlour Defermented With Cow Rumen Liguor In DietFor Asian Redtail Catfish (Hemibagrus nemurus) - Riko Martinus S; Adelina Adelina; Indra Suharman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstrak   This research was conducted on September-November 2018. The purpose of this study to find out the use of fermented mustard and cabbage wastesflour (FMCWF)in diet on feed digestibility, feed efficiency and growth ofAsian redtail catfish (Hemibagrus nemurus). The method used is using a completely randomized design (CRD) with five treatments and three replications. The treatment applied in the study is P0 (100: 0%), P1 (95: 5%), P2 (90: 10%), P3 (85: 15%) and P4 (80: 20%). The results showed fermentation of mustard and cabbage wastes flour had an effect on feed efficiency, protein retention, specific growth rate. The best treatment is feed containing 20% fermented mustard and cabbagewaste flour which produces feed digestibility68.55%, protein digestibility 76.32%, feed efficiency 37.71%, protein retention 32.27%, specific growth rate 3.43% and survival rate 96.6%. The results of measurements of water quality during the study, namely temperatures of 26-30oC, pH ranged from 6-8, DO 4.2-4.5 mg/L and ammonia 0.001 ppm. Keywords : Fermentation, (Hemibagrus nemurus), Mustard and Cabbage waste